Eksistensi Budaya Sasi Laut Terhadap Pelestarian Ekosistem Mangrove Dan Ekowisata Desa Taar Kota Tual - Kopong, Maria M.; Sukirno, Pradina Anjarwaty; Renjaan, Melissa Justin; Betaubun, Kemilius Deleles; Renjaan, Meiksyana Raynold (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the existence of the "sasi" culture in the preservation of mangrove ecotourism in Taar Village, Tual City, to find out the "sasi" rules that apply to mangrove ecotourism in Taar Village, Tual City. The types of data used are primary data and secondary data. Informants in this study are the Taar Village Community, and key informants in this study are the Taar Village Apparatus. The research method used in this study is a qualitative research method. The results of the study indicate that the sea sasi culture not only contributes to mangrove conservation, but also increases public awareness of the importance of protecting the environment. In addition, ecotourism based on sea sasi practices provides benefits to local communities. Thus, the existence of sea sasi culture can function as a model for harmonious natural resource management between the environment and increasing public awareness of sea sasi culture towards the preservation of mangrove ecotourism.